Multi-scale transport and exchange processes in the atmosphere over mountains Programme and experiment - Serafin, Stefano (innsbruck university press, 2020)
TEAMx (www.teamx-programme.org) is an international research programme that aims at improving the understanding of exchange processes in the atmosphere over mountains at multiple scales and at advancing the parameterizations of these processes in numerical models for weather and climate prediction. This document, compiled by the TEAMx Programme Coordination Office, provides a concise overview of the scientific scope of TEAMx.; TEAMx (www.teamx-programme.org) ist ein internationales Forschungsprogramm, das darauf abzielt, das Verständnis von Austauschprozessen in der Atmosphäre über Bergen auf mehreren Ebenen zu verbessern und die Parametrisierung dieser Prozesse in numerischen Modellen für die Wetter- und Klimavorhersage voranzutreiben. Dieses vom TEAMx-Programmkoordinierungsbüro zusammengestellte Dokument bietet einen kurzen Überblick über den wissenschaftlichen Umfang von TEAMx.